BUDDHIST CAUSALITY AND THE FORTUNE-TELLING PRACTICES IN URBAN CHINA: A MIXED-METHODS STUDY OF KARMA–VIPĀKA INTEGRATION IN DIVINATORY DISCOURSE - Guangliang HOU; Chompoo Gotiram (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This article examines how Mahāyāna Buddhist causality—specifically, the triadic concepts of karma, vipāka, and pratītyasamutpāda—is operationalized within the symbolic and discursive systems of contemporary Chinese fortune-telling. Drawing on textual analysis, semi-structured interviews with fifteen diviners, a quantitative survey of 278 clients, and longitudinal case studies, this study proposes a five-layer "divination–causality integration model." Findings demonstrate that Buddhist karmic logic, especially the "cause–condition–result" schema, is embedded in both interpretive frameworks and ritual interventions. Clients' endorsement of karmic beliefs correlates with improved emotional adjustment, more transparent decision-making, and more ethical conduct. This research contributes to the sociology of religion, psychological anthropology, and contemporary Buddhist studies by revealing how doctrinal teachings are reframed as therapeutic tools in late-modern Chinese society. The study further recommends incorporating Buddhist causal reasoning into culturally grounded mental health interventions and digital divinatory technologies.